Lifetimes of mRNA molecules directing the synthesis of viral proteins in herpes simplex virus-infected cells. - Ward, R L (1975)
Possible variations in the functional lifetimes of herpes simplex virus type 1 mRNA molecules in infected HeLa cells were studied. As shown by the rate of decrease of radioactive amino acid incorporation into viral proteins after the addition of actinomycin, the average lifetime of early viral mRNA's are shorter than those for the late messenger species. In addition, when the viral proteins made after the addition of actinomycin were further analyzed by gel electrophoresis, it was found that messengers for individual viral proteins translated within the early or late time period also had some differences in their functional lifetimes. These results indicate that the synthesis of herpes simplex virus type 1 proteins during the replicative cycle is regulated in part by mechanisms controlling the functional lifetimes of viral mRNA's.